Analysis of Microwave-Assisted Heating of Deep Eutectic Solvent: Thermal and Cosmo-Rs Study - Zuniga-Navarro, G; Quijada-Maldonado, E; Olea-Chandia, F (Elsevier B.V., 2025)
This study examines the heating behavior, thermal stability, and energy conversion efficiency of hydrophilic and hydrophobic Deep Eutectic Solvents (DES) when exposed to 2.45 GHz microwave radiation at a constant power of 405 W in an industrial oven. All DES were synthesized under controlled vacuum conditions, and their thermal and physical properties were characterized experimentally. Theoretical predictions of dielectric constants and polarity were obtained using COSMO-RS simulations. The heating behavior of DES was evaluated by monitoring temperature rise as a function of irradiation time, while thermal stability was analyzed using thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), and Fourier-transform infrared spectroscopy (FTIR). Results suggest that the viscosity of DES significantly influences heating rates, with low-viscosity DES showing a rapid and energy-efficient temperature rise. Dielectric constants and polarity predicted by COSMO-RS aligned with the observed trends in microwave absorption. Additionally, TGA analyses confirmed that DES maintained thermal stability when heated below their degradation temperatures, as evidenced by negligible chemical changes in FTIR spectra after repeated heating cycles. Furthermore, the conversion of electrical work into thermal energy was substantially more efficient under microwave heating compared to conventional conductive heating. This work demonstrates that viscosity and polarity critically impact microwave energy absorption, supporting the use of DES as an efficient and stable media for microwave-assisted applications. © 2025 Elsevier B.V.
Keywords: COSMO- RS; Deep eutectic solvents; Loss tangent; Microwave heating